(3HGchQI GdRHOI ef JGQjN BSaj hYHOIs - (3CHh GdYHGS CMeO Hf eMeO GdUHjMji GdSdGhj,J (B1363 (3g` s
(3ChdgG (B:s
(3CeG HYO , ajbhd CMeO Hf eMeO GdUHjMi GdSdGhi bO WdH efi HYV CaGVd GdeMHjf GdPjf jJYjf Ydi ESYGage Cf CcJH Yf eOjfI BSai hbHjdI YHOI s
(3BNQgG (B:s
(3gGgfG bO ced eG CQOfG LeYg ef HGchQI GdRHOI ef JGQjN BSai hYHOI , eSJdaJjf fXQ cd hGba Ydjg Edi eG bOefGg ai GdOjHGLI Hjf jOjg hGddg CYde s
(3cJHJ Hbde ajg VHWs
(3HChdgG agQS ddehVhYGJs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B251 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B285s
Keywords: (3GdJGQjNs